On the Timing of Education - Anna Sjögren; Maria Saez-Marti (The Research Institute of Industrial Economics (IUI), 2004)
We propose a simple investment model which shows that, in the presence of fluctuations in and uncertainty about the opportunity cost of time, marginal individuals may choose to delay their education if the opportunity cost of time is temporarily high. Importantly, it is when the completion of the degree is uncertain, but likely enough that individuals will consider delaying their education. As a result, when returns to education are relatively low, education and timing of education will be sensitive to fluctuations in the opportunity cost of time. If return is high, delay is never optimal. These findings are supported by Swedish university enrolment patterns, and cross-country evidence on age of university freshmen.
Keywords: D81; J22; J24; 330; Timing of Education; Fluctuating Opportunity Costs; Bildungsökonomik; Bildungsverhalten; Zeitpräferenz; Opportunitätskosten; Theorie; Studium; Schweden